User’s Switching Intention from Social Media Freemium to Premium - Nabila Clydea Harahap; Luthfi Alnazhary; Shehaanmakya Muhammad Sutoyo Reksohaminoto; Zundullah B. Djibat; Putu Wuri Handayani (Faculty of Computer Science Universitas Indonesia, 2025)
To date, social media platforms offer many exclusive or special features for making payments on these premium platforms. This study aims to identify the push, pull, and mooring factors that influence users’ intention to switch from freemium to premium social media in Indonesia, drawing on the push-pull-mooring (PPM) theory. An online questionnaire involving 507 social media users in Indonesia and in-depth interviews with 30 users were conducted, with the qualitative data analyzed using content analysis to enrich the quantitative findings. The results show that functionality, advertising intrusiveness, relative advantage, price value, switching cost, and social influence influence switching intention. Theoretically, this study contributes to the PPM framework and the concept of switching intention by extending them to the context of user transitions from freemium to premium social media platforms in Indonesia, a context that has not been previously explored. Practically, the findings provide guidelines for social media platforms to improve premium features and enhance service offerings.